Selectivity Adsorption of Anionic Dyes by Macroalgae E. cottonii - Bunga Indah Putri (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2024)
The selectivity analysis of anionic dye adsorption by E. cottonii macroalgae has been successfully conducted in this study. Selectivity analysis encompassed congo red, direct yellow, methyl orange, and direct green dyes with measurements taken at 0, 2, 4, 6, 8, and 10-minute intervals. The dye concentration was standardized at 50 g/mL, and 20 mL of each dye solution was utilized. Variations in absorbance were assessed using a UV-Vis Spectrophotometer, revealing that E. cottonii exhibited the highest selectivity for methyl orange. Characterization through FT-IR indicated the presence of O-H, C-H aliphatic, C=N, C=C, C-O, and N-H bonds in the dried E. cottonii macroalgae material. These results affirm the superior selectivity of E. cottonii in adsorbing methyl orange, as demonstrated by the selectivity test.